2010
DOI: 10.1007/s00109-010-0695-1
|View full text |Cite
|
Sign up to set email alerts
|

Variation in amount of wild-type transthyretin in different fibril and tissue types in ATTR amyloidosis

Abstract: Familial transthyretin (TTR) amyloidosis is caused by a mutation in the TTR gene, although wild-type (wt) TTR is also incorporated into the amyloid fibrils. Liver transplantation (LT) is the prevailing treatment of the disease and is performed in order to eliminate the mutant TTR from plasma. The outcome of the procedure is varied; especially problematic is a progressive cardiomyopathy seen in some patients, presumably caused by continued incorporation of wtTTR. What determines the discrepancy in outcome is no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 81 publications
(75 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…Although previous studies have shown a good correlation between MBF based on 11 C-acetate and MBF as measured by 13 N-ammonia (20) and 15 O-water (19), both in healthy controls and patients with hypertrophic cardiomyopathy, the use of 11 C-acetate for MBF measurements in amyloidosis patients has not been validated. A possible explanation for the low apparent MBF in the patient group could be partial-volume effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Although previous studies have shown a good correlation between MBF based on 11 C-acetate and MBF as measured by 13 N-ammonia (20) and 15 O-water (19), both in healthy controls and patients with hypertrophic cardiomyopathy, the use of 11 C-acetate for MBF measurements in amyloidosis patients has not been validated. A possible explanation for the low apparent MBF in the patient group could be partial-volume effect.…”
Section: Discussionmentioning
confidence: 99%
“…They are not scarred tissue but nonfunctional, probably nonperfusable, myocardium with a mechanical restriction, resulting in a reduced apparent transmural MBF as measured by 11 C-acetate, because the kinetic model measures the mean perfusion in both perfusable and nonperfusable tissue. It may well be the case that MBF is normal in remaining perfusable tissue, and future studies will include MBF measurements with 15 O-water, with which MBF measurements solely in perfusable tissue can be obtained as well (27).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical analysis revealed that amyloid deposits in the ligamentum flavum of lumbar spinal canal stenosis patients consisted of C-terminal transthyretin fragments, which constantly occur in amyloid deposits in senile systemic amyloidosis, in addition to full-length transthyretin. 21,23 Although the roles of transthyretin fragmentation in amyloid formation remain to be clarified, there may be a common pathologic process for transthyretin amyloid formation in the ligamentum flavum of lumbar spinal canal stenosis patients and that in senile systemic amyloidosis. The small spotty transthyretin-negative amyloid deposits were more frequently seen in younger patients, but precursor proteins of those amyloid deposits remain to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…A polyclonal antiserum against truncated transthyretin 50-127 (transthyretin 50-127), produced in rabbits, was diluted 1:2000 and used as the primary antibody. 21 A goat anti-rabbit antibody conjugated with horseradish peroxidase (Dako), diluted 1:5000, was used as the secondary antibody. The reaction was visualized by using an enhanced chemiluminescence system (GE Healthcare, Buckinghamshire, UK).…”
Section: Detection Of Fragmented Transthyretin In Amyloid Depositsmentioning
confidence: 99%